Effects of adding a spray-dried polyclonal antibody preparation on ruminal fermentation patterns and digestibility of cows fed high concentrate diets - Bastos, Joao Paulo S. T. [UNESP]; Marino, Carolina T.; Millen, Danilo D. [UNESP]; Pacheco, Rodrigo D. L.; Diniz-Magalhaes, Juliane; Perna, Flavio; Martins, Cyntia Ludovico [UNESP]; Rodrigues, Paulo Henrique M.; Arrigoni, Mario D. B. [UNESP] (Pagepress Publ, 2012)
The present study aimed to evaluate the effects of different doses of a spray-dried polyclonal antibody preparation against specific ruminal bacteria on rumen fermentation parameters as well as protozoa counts, in situ degradability of sugarcane neutral detergent fibre (NDF) and total tract apparent digestibility of total diet in cows fed high concentrate diets. Eight ruminally-cannulated cows were used in a replicated 4 4 Latin square design with four experimental periods of 21 days. The treatments were: T1 (control), 0.0 g/d of multivalent polyclonal antibody preparation (PAP-MV); T2, 1.5 g/d of PAP-MV; T3, 3.0 g/d of PAP-MV; T4, 4.5 g/d of PAP-MV. Sample collection for rumen fermentation parameters was carried out the last day of each period at 0, 2, 4, 6, 8, 10 and 12 h after morning meal. For protozoa counts, samples were collected the last day of each period at 0 and 4 h after feeding. In situ degradability of sugarcane NDF was performed the last 5 days of each period, while total tract apparent digestibility of total diet was assessed the last 10 days of each period. Regardless of sampling time, there was no linear or quadratic effect on rumen pH, total concentration of short chain fatty acids, molar proportion of acetate, propionate and butyrate, ammonia nitrogen (NH3-N) or lactate. No treatment effects were detected for protozoa counts, in situ degradability of sugarcane NDF and total tract apparent digestibility of total diet. In conclusion, different levels of spray-dried PAP-MV were not sufficient to alter rumen environment.
Keywords: Feed additive; pH; Rumen; Short chain fatty acids